Dispersion of Third‐Harmonic Generation in Organic Cavity Polaritons. Issue 18 (30th May 2019) - Liu, Bin; Crescimanno, Michael; Twieg, Robert J.; Singer, Kenneth D.
Abstract: Organic cavity polaritons are bosonic quasiparticles arising from the strong interaction between organic molecular excitons and photons within microcavities. The spectral dispersion of third‐harmonic generation near resonance with cavity polaritons is studied experimentally via angle‐resolved reflected third‐harmonic generation measurements with several pump wavelengths. Moreover, a three‐step nonlinear optical transfer matrix model is used to simulate the third‐harmonic generation using the sum‐over‐states dispersive nonlinear coefficients, which include polariton states. The angle‐dependent experiment and modeling agree, revealing the output of third‐harmonic generation is resonantly enhanced when third‐harmonic wavelengths are near upper polaritons. Lower‐polariton‐enhanced third‐harmonic generation is not experimentally observed due to inadequate coupling at the longer wavelength, which is also consistent with the nonlinear transfer matrix modeling. These results indicate that the sum‐over‐states nonlinear dispersion is descriptive of the nonlinear optical process so that the polariton states belong to a complete set of states for a perturbative determination of the nonlinear optical response. From these results, it might be expected that such a basis for perturbation theory would be widely applicable for nonlinear optical processes in the strong and ultrastrong limits. The results also indicate the possibility of wavelength agile nonlinear optical response by angle‐of‐incidence tuning. Abstract : The dispersion of third‐harmonic generation is studied near the upper‐polariton branch of an optical cavity containing an organic glass. Both the angle and wavelength dependence of the third‐harmonic generation are measured and compared with a nonlinear transfer matrix model indicating that the dispersion is described by the sum‐over‐states nonlinear susceptibility model having poles associated with the polariton branch.